UTILIZATION FLOUR OF WHITE SHRIMP SHELL (Litopenaeus vannamei) AS FLAVOR WITH ADDITION OF DEXTRIN AND APLICATION IN TARO CHIPS - Wirawan, Purnama; Sari, N. Ira; ', Desmelati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThis research was aimed to determine the addition of shrimp shell flour as flavorin taro crisp and also to increase the taste for consumer. The result indicated thatutilization of white shrimp (Litopenaeus vannamei) shell flour as flavor in tarocrisp was significantly effect by consumer acceptance in taste and proximatanalysis with 60 panelist (85%). The treatment with adding 10% of dextrin andseasoning (P3) was the best treatment with organoleptic characteristic qualityreddish white in appearence, scent and taste to shrimp, and strongly seasoning.Proximat analysis for moisture content 6.61%, fat content 2.17% and ash content2.99%.Keywords: shells of shrimp, dextrin, taro chips.